Iron Efflux from Oligodendrocytes Is Differentially Regulated in Gray and White Matter - Katrin Schulz; Chris D. Vulpe; Z. Leah Harris; Samuel David (2011)
Accumulation of iron occurs in the CNS in several neurodegenerative diseases. Iron is essential for life but also has the ability to generate toxic free radicals if not properly handled. Iron homeostasis at the cellular level is therefore important to maintain proper cellular function, and its dysregulation can contribute to neurodegenerative diseases. Iron export, a key mechanism to maintain proper levels in cells, occurs via ferroportin, a ubiquitously expressed transmembrane protein that partners with a ferroxidase. A membrane-bound form of the ferroxidase ceruloplasmin is expressed by astrocytes in the CNS and regulates iron efflux. We now show that oligodendrocytes use another ferroxidase, called hephaestin, which was first identified in enterocytes in the gut. Mice with mutations in the hephaestin gene (sex-linked anemia mice) show iron accumulation in oligodendrocytes in the gray matter, but not in the white matter, and exhibit motor deficits. This was accompanied by a marked reduction in the levels of the paranodal proteins contactin-associated protein 1 (Caspr) and reticulon-4 (Nogo A). We show that the sparing of iron accumulation in white matter oligodendrocytes in sex-linked anemia mice is due to compensatory upregulation of ceruloplasmin in these cells. This was further confirmed in ceruloplasmin/hephaestin double-mutant mice, which show iron accumulation in both gray and white matter oligodendrocytes. These data indicate that gray and white matter oligodendrocytes can use different iron efflux mechanisms to maintain iron homeostasis. Dysregulation of such efflux mechanisms leads to iron accumulation in the CNS.